Neonatal cerebral sinovenous thrombosis: Two cases, two different gene polymorphisms and risk factors - Turan, Özden; Anuk-İnce, Deniz and Olcay, Lale and Sezer, Taner and Gülleroğlu, Kaan and Yılmaz-Çelik, Zerrin and Ecevit, Ayşe (The Turkish Journal of Pediatrics, 2017)
Cerebral sinovenous thrombosis (CSVT) is a rare disease in the neonatal period and also the greatest risk of neonatal mortality and morbidity. In this report, we presented two cases with CSVT and different risk factors. One of these cases had methylenetetrahydrofolate reductase (MTHFR) C677T homozygous polymorphism and the other case had both MTHFR A1298C homozygous polymorphism, plasminogen activator inhibitor-1 (PAI-1) 4G/ 5G polymorphism and elevated lipoprotein a. Early diagnosis and prompt initiation of therapy of neonatal CSVT may prevent neonatal mortality and poor long-term neurodevelopmental outcomes.